Mechanical properties and nanostructure of monolithic zeolitic imidazolate frameworks: a nanoindentation, nanospectroscopy, and finite element study - Tricarico, M; Tan, J-C (Elsevier, 2021)
The synthesis of metal-organic frameworks (MOFs) in a monolithic morphology is a promising way to achieve the transition of this class of materials from academia to industrial applications. The sol-gel process has been widely used to produce MOF monoliths. It is relatively cheap and simple compared with other techniques (e.g. mechanical densification), and moreover, it allows to produce ‘pure’ monoliths, that is, without the need of using binders or templates that could affect the functional properties of the MOF. Understanding the mechanical properties of these monoliths is crucial for their transit to practical applications. We studied the mechanical behavior of two zeolitic imidazolate frameworks (ZIF-8 and ZIF-71) by means of instrumented nanoindentation and atomic force microscopy (AFM). Tip force microscopy (TFM), an extension of AFM, was used to reveal the surface nanostructure of the monoliths. We used finite element (FE) simulations alongside the experiments, to establish a suitable constitutive model and determine an improved estimate of the yield stress (σY) of ZIF monoliths. Nano-Fourier-transform infrared (nano-FTIR) spectroscopy was subsequently used to pinpoint local structural alteration of the framework in the contact area. The combination of TFM, FE simulations, and nano-FTIR enabled us to identify the mechanical deformation mechanisms in monolithic ZIF materials: grain boundary sliding is dominating at low stresses, then breakage of chemical bonds and a partial failure of the framework occur, eventually leading to a densification of porous framework at the contact zone. Finally, we measured the fracture toughness using a cube corner indenter to study the resistance of monoliths against cracking failure.